Fiscal indicators - Larch, Martin; Martins, Joao Nogueira; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
Fiscal indicators are the backbone of effective fiscal policy-making, including the coordination and surveillance of budgetary policy at the EU level. The Workshop organized by the Directorate-General for Economic and Financial Affairs of the European Commission on 22 September 2006 in Brussels aimed at enriching the debate on the fiscal indicators and improving the understanding of their functioning. In this Economic Paper we publish the proceedings of the workshop. On top of a brief introduction which puts the topics into perspective, the volume collects all the contributions presented and discussed at the workshop. Mirroring the structure of the workshop the proceedings are organised in the parts: (i) long-term sustainability, (ii) the measurement of the underlying budgetary position and discretionary fiscal policy and (iii) the reliability of fiscal indicators.
Economic Papers